Professionally-Oriented Tasks as a Component of Fundamental Mathematical Training of Students of Technical Universities and Colleges - Alyona Kolomiets; Vitaliy Klochko; Olena Stahova (Pedagogical Discourse, 2019)
The article reveals the essence of the task concepts, a professionally-oriented task, analyzes the problem of introducing professionally-oriented tasks into the educational process as the main component of the fundamental mathematical training of graduates of technical universities and colleges.The mathematical competencies proposed by national and international researchers are analyzed; on the basis of the analysis are performed, the mathematical competences of technical specialists are emphasized: logical and analytical, visual and imaginative, informational computational, research; intelligent, constructive, prognostic. The list of professionally-oriented mathematical competencies has been suggested that are the criteria for fundamental mathematical training: conceptual, operational and algorithmic, applicable, constructive.A comparative analysis of the core competencies of the future specialists in technical specialties of universities and colleges has been carried out; on the basis of this analysis, a conclusion has been determined about the identity of the acquired professional-oriented mathematical competences of graduates of universities and colleges.The main types of activities that students carry out during solving professional-oriented tasks are analyzed: analytical, graphical and computational, research, their influence is given by forming professional-oriented mathematical competences. The study lists the main requirements for professionally-oriented mathematical problems: the content of the problem should be real, reveal the practical significance and importance for the student of the mathematical knowledge obtained, the solution should be based on knowledge from various special disciplines and is aimed at the specific application of real content, the tasks should describe the situation, approximate to the future field of professional activity, the numerical data in the problem should correspond to the real. The article presents an example of a professionally-oriented task, analyzes the relationship between the solution of professionally-oriented tasks and the formation of professionally-aimed mathematical competences, and reached conclusions about the feasibility of using professionally-oriented tasks in the educational process.